2014
DOI: 10.1371/journal.pone.0094997
|View full text |Cite
|
Sign up to set email alerts
|

An Agomir of miR-144-3p Accelerates Plaque Formation through Impairing Reverse Cholesterol Transport and Promoting Pro-Inflammatory Cytokine Production

Abstract: AimsATP-binding cassette transporter A1 (ABCA1) mediates the efflux of cholesterol and phospholipids to lipid-poor apolipoproteins, which then form nascent HDL, a key step in the mechanism of reverse cholesterol transport (RCT). While a series of microRNAs (miRNAs) have been identified as potent post-transcriptional regulators of lipid metabolism, their effects on ABCA1 function and associated mechanisms remain unclear.Methods and ResultsABCA1 was identified as a potential target of miR-144-3p, based on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
80
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 49 publications
2
80
0
2
Order By: Relevance
“…miRNAs function via base pairing with complementary sequences within mRNA molecules [20,21,22,23], cutting off the mRNA molecule on target genes, or inhibiting translation of target genes. Some research has indicated that miR-144 is downregulated in many cancers [24,25,26,27,28,29,30,31]. These previous findings coincide with our results, which identified that miR-144 is significantly downregulated in human lung cancer.…”
Section: Discussionsupporting
confidence: 92%
“…miRNAs function via base pairing with complementary sequences within mRNA molecules [20,21,22,23], cutting off the mRNA molecule on target genes, or inhibiting translation of target genes. Some research has indicated that miR-144 is downregulated in many cancers [24,25,26,27,28,29,30,31]. These previous findings coincide with our results, which identified that miR-144 is significantly downregulated in human lung cancer.…”
Section: Discussionsupporting
confidence: 92%
“…These findings indicate that miR-144-3p may be a potential therapeutic target of atherosclerosis. Furthermore, clinical studies have shown a positive correlation between circulating miR-144-3p and serum creatine kinase, lactate dehydrogenase and aspartate aminotransferase in subjects with AMI [46].…”
mentioning
confidence: 98%
“…A common feature for several of the differentially expressed miRs (miR-26a-5p, miR-106a-5p, miR-144-3p and miR-148b-3p) are their mutual target, the ATP-binding cassette, sub-family A, member 1 (ABCA1) [46,[61][62][63][64]. ABCA1 is the major regulator of cellular cholesterol and fundamental to the initiation and progression of atherosclerosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-33 deletion has been shown to result in worsening of obesity and liver steatosis in rodent models [99]. MiR-144-3p has also been shown to target ABCA1, agomirs of which inhibited foam cell cholesterol efflux in vitro and led to an acceleration of atherosclerosis in ApoE-/- mice in vivo [100]. Furthermore, circulating miR-144-3p levels correlated with serum creatine kinase, lactate dehydrogenase and aspartate aminotransferase in patients with acute MI.…”
Section: Mirnas In Clinical Studies In Atherosclerosismentioning
confidence: 99%